CONFERENCES AND SYMPOSIA : Electron guns at the Budker Institute of Nuclear Physics SB RAS: prospects for the use of photocathodes with nanosecond and subpicosecond laser drivers. (2nd January 2018) - Vinokurov, N A; Barnyakov, A M; Volkov, V N; Kolobanov, E I; Kuznetsov, G I; Kurkin, G Ya; Levichev, A E; Logachev, P V; Nikiforov, D A; Petrov, V M; Starostenko, D A; Tribendis, A G
Abstract: The problem of producing high-current electron beams with relatively small lateral sizes and small velocity spread is more than a hundred years old. The continuous improvement of near-ultraviolet electromagnetic radiation sources (lasers with harmonics generators) allows significantly improving the parameters of existing electron guns. This paper discusses some problems in the development of electron guns with photocathodes and considers possible ways of using laser photocathodes in the electron guns designed at the Budker INP SB RAS.